Statin effects on atherosclerotic plaques: regression or healing?. Issue 1 (December 2015) - Bittencourt, Marcio; Cerci, Rodrigo
Abstract Despite the well-documented improved survival of coronary heart disease with the use of statins, their effects on atherosclerotic plaques are not yet fully understood. While some studies suggest statins may reduce plaque volume, the reduction is small even with the use of high-dose statins. Due to this small change in plaque volume, other effects of statin therapy on plaques have been proposed. A large meta-analysis by Banach et al. explored statin effects on plaque composition detected by intravascular ultrasound (IVUS). We discuss the mechanisms of plaque composition modification demonstrated in their study and its implications on atherosclerotic plaque stabilization. ᅟ Please see related article:http://www.biomedcentral.com/1741-7015/13/229 .